Genetic analyses reveal cryptic diversity in the widely distributed Styela canopus (Ascidiacea:Styelidae) - Barros, R. C.; Rocha, R. M. (Invertebrate Systematics, 2021)
The routine use of DNA sequencing techniques and phylogenetic analysis has resulted in the discovery of many cryptic species, especially in the oceans. The common, globally introduced species Styela canopus is suspected to be a complex of cryptic species because of its widespread distribution and variable external morphology. We tested this possibility using COI and ANT marker sequences to uncover the phylogenetic relationship among 19 populations, and to examine genetic variability as well as gene flow. We obtained 271 COI and 67 ANT sequences and found surprising diversity among the 19 populations (COI: p = 0.18, hd = 0.99; ANT: p = 0.13, hd = 0.95). Corresponding topologies were found using Bayesian inference and maximum likelihood for both simple locus (COI) and multilocus (COI + ANT) analyses and so the clades received strong support. We used simple (ABGD, bPTP, GMYC) and multiple (BSD) locus methods to delimit species. The simple locus methods indicated that the current Styela canopus comprises at least 15 species. The BSD method for concatenated data supported 7 of the 15 species. We suggest that S. canopus should be treated as the Styela canopus complex. The large number of cryptic species found, often with more than one clade found in sympatry, creates opportunities for better understanding reproductive isolation, hybridisation or speciation. As several lineages have already been introduced widely around the world, we must quickly understand their diversity and invasive abilities.